When western leadership models become a mixed blessing - Reimer, J. (2010)
Russia plunged into a deep leadership crisis after the collapse of the Soviet Union. The attempt to implement western leadership models only deepened the crisis. With the take over of power by Vladimir Putin a new leadership theory evolved, which looked critically at western models. Totalitarianism, contextuality, cultural sensibility and pragmatism are issues being investigated with respect to leadership. This article includes these themes whilst reflecting on the critical dialogue between the American leadership expert Stephen R. Covey and his Russian critic Vladimir Tarassenko.
Keywords: Russia; Perestroika; Leadership; Culturally Relevant Leadership